Overcurrent and ground fault relay protection settings at tranformator-1 150kV/20kV Braga substation - Rusiana Iskandar, Handoko; Mulyono, Herry; Charisma, Atik; Hidayat, Muhammad Reza (Jurusan Teknik Elektro, Politeknik Negeri Bandung, 2023)
The occurrence of a malfunction at the substation results in power outages and losses in the electrical energy distribution system to consumers. Many tests are carried out to see the performance of the protection system, including the parameters of the over current relay (OCR) and ground fault relay (GFR) in the electrical energy distribution system. This research aims to analyze OCR and GFR values, analyze OCR setting, drop-off, and pick-up values, and analyze OCR time characteristics using DigSilent Power Factory 15.1 software based on existing equipment specification data at the Braga substation. The results show an OCR accuracy level of around 94% on the 20 kV and 150 kV sides. Meanwhile, 92.39% on the 20 kV GFR side and 94.87% on the 150 kV side. The setting value for the pick-up current is 0.92 A on the 20 kV side of the GFR and the drop-off current is 0.85 A on the 150 kV side with a pick-up current of 0.39 A and a drop-up current of 0.37 A. Setting a value on the 20kV side is greater than on the 150 kV side due to the difference in current transformer ratio values. The simulation results show that the OCR and GFR characteristic curves on both sides meet the criteria for a protection system with good performance.